SABATAYİZMİN AVRUPA YAHUDİLİĞİNE ETKİLERİ - (:unkn) unknown (My University, 2012)
17. yüzyılda Osmanlı Devletinde ortaya çıkan Sabatayist hareket büyük oranda Osmanlı toprakları dışındaki Avrupa Yahudiliğinde etkili olmuştur. Mesihlik fikri, eskatolojik fenomenler, siyona dö- nüş gibi birtakım Yahudi inançları Sabatayizm etkisi altında geliş- miştir. Ayrıca Doğu Avrupada Frankizm adıyla bilinen bir konverso Yahudi yaşamı da doğrudan doğruya Sabatayizmin etkisi altında şekillenmiştir.

Sabbatean movement that emerged in XVII century in the Otto- man Empire has effects mostly on the European Judaism which is outside of Ottoman lands. Jewish beliefs such as the idea of Mes- sianic, eschatological phenomena, return to Zion, and etc. have developed under the influence of Sabbatean movement. A conver- so Jewish life style which is known as Frankism in East Europe al- so formed directly under the influence of Sabbatean movement.
The Effects of Sabbateans on European Judaism
Keywords: Tarih